Sosialisasi UU ITE di SMAN 1 Wirosari: Meningkatkan Kesadaran Hukum Generasi Muda - Indah Dwi Murdianingsih; Hadi Tanuji (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The misuse of the internet among teenagers has become a major concern in this digital era, particularly regarding the spread of hoax news and cyber law violations. Therefore, a socialization program on the Law on Electronic Information and Transactions (UU ITE) was conducted at SMAN 1 Wirosari to enhance students' legal awareness in utilizing digital technology. This activity involved 90 participants, consisting of OSIS administrators and Class Representative Council (MPK) members. Through interactive lectures, discussions, and case simulations, this socialization successfully improved participants' understanding of UU ITE and its impact on daily life. Evaluations showed that after this activity, students had a better grasp of the importance of critical thinking and responsible digital media usage